Gonadal development and induced spawning in spontaneously bred Labeo rohita (Ham.) - Rath, S C; Sarkar, S K; Gupta, S D; Mondal, B (Indian Journal of Fisheries, 2011)
Mass spontaneous spawning of Catla catla, Labeo rohita, L. calbasu and Cirrhinus mrigala in selected ponds of the Orissa state fish farm at Kausalyaganga was recorded. Of the above four species, spent brood of L. rohita was studied further for subsequent gonadal development and second breeding.GSI (ovary) of spent L. rohita after spontaneous spawning was recorded as 2.04 + 0.093, whereas the same in non-bred brood of the adjacent pond was recorded as 17.56 + 1.35. GSI of the spent female increased to 8.26 + 0.391 after 15 daysof spontaneous spawning and the same after 45 days was 14.1 + 0.2. Histomorphology of ovary on the first day after spontaneous spawning exhibited 74 % empty follicles and 26 % unspawned oocytes of different stages. After 15days of spontaneous spawning, the spent ovary showed many newly recruited oogonia, some developing oocytes and few atretic follicles. Ovary after 45 days of spontaneous spawning had mostly maturing and matured oocytes along withsome traces of resorbing atretic follicles. The spent brood could be induced bred second time in eco-hatchery system after 60 days. The spontaneously bred L. rohita on its second breeding produced 0. 92 x 105 spawn per kg body weight, whereas non-bred (control) brood produced 0.71 x 105 spawn per kg body weight. The fecundity and fertilization rate in second breeding were higher, 1.2 x 105 and 94-96 % respectively than 0.91x 105 and 88-90 % of the control.